Field measurements of fugitive methane emissions from three Australian waste management and biogas facilities. (1st January 2022) - Reinelt, Torsten; McCabe, Bernadette K.; Hill, Andrew; Harris, Peter; Baillie, Craig; Liebetrau, Jan
Highlights: We detected and quantified CH4 emissions from Australian biogas plants. We compared Australian and European AD technology with regard to CH4 emissions. We tested an instrument to screen precisely emission hot spots on landfills. Abstract: A key environmental sustainability requirement for the treatment of organic waste via anaerobic digestion (AD) is the prevention of unwanted methane emissions in the production chain whenever possible. Identifying and quantifying these emissions has been frequently investigated, particularly in Europe. However, the challenges of climate change are also becoming vitally important in Australia. This novel study presents the results from emission measurement campaigns carried out at two biogas plants and one landfill site in Australia. An on-site approach consisting of leakage detection and emission quantification by a static chamber method was applied. Twenty-nine leakages were detected predominantly on the digesters (gastight covered anaerobic lagoons) of the biogas plants. Ten emission hot spots were found on the surface cover of a landfill site. Methane emission rates of 9.9 ± 2.3 kg h −1 (10.5 ± 2.4% CH4 ) for biogas plant A, 3.0 ± 1.9 kg h −1 (8.1 ± 5.2% CH4 ) for biogas plant B and 41–211 g h −1 for the two largest emission hot spots from the landfill were measured. Since not every single leakage or hot spot could be quantified separately, the stated overall emission rates had to be extrapolated. Importantly, the emission rates from the landfill should be interpreted carefully due to the limited overall area which could be practicably investigated. Leakages occurred at common components of the covered anaerobic lagoons such as the membrane fixation or concrete walls. Repairing these parts would increase the plant safety and mitigate negative environmental effects.